Traduire la science-fiction - Alice Ray (ReS Futurae)
Translation plays an essential role in the development and evolution of the science fiction genre, but it is a relatively unexplored area of research in translation studies. These few pages introduce the “Science fiction & translation” issue by revealing the challenges entailed in translating the genre and by giving a few academic benchmarks in order to contextualise the articles within a constantly evolving state of the art and to discuss the aim of such a thematic issue.